The ICU Mobility Scale Has Construct and Predictive Validity and Is Responsive A Multicenter Observational Study - Tipping, C.; Bailey, M.; Bellomo, R.; Berney, S.; Buhr, H.; Denehy, L.; Harrold, Megan; Holland, A.; Higgins, A.; Iwashyna, T.; Needham, D.; Presneill, J.; et al. (2016)
Rationale: The ICU Mobility Scale (IMS) is a measure of mobility milestones in critically ill patients. Objectives: This study aimed to determine the validity and responsiveness of the IMS from a prospective cohort study of adults admitted to the intensive care unit (ICU). Methods: Construct and predictive validity were assessed by comparing IMS values at ICU discharge in 192 patients to other variables using Spearman rank correlation coefficient, Mann-Whitney U tests, and logistic regression. Responsiveness was assessed using change over time, effect size, floor and ceiling effects, and percentage of patients showing change. Measurements and Main Results: The IMS at ICU discharge demonstrated a moderate correlation with muscle strength (r = 0.64, P < 0.001). There was a significant difference between the IMS at ICU discharge in patients with ICU-acquired weakness (median, 4.0; interquartile range, 3.0–5.0) compared with patients without (median, 8.0; interquartile range, 5.0–8.0; P < 0.001). Increasing IMS values at ICU discharge were associated with survival to 90 days (odds ratio [OR], 1.38; 95% confidence interval [CI], 1.14–1.66) and discharge home (OR, 1.16; 95% CI, 1.02–1.32) but not with return to work at 6 months (OR, 1.09; 95% CI, 0.92–1.28). The IMS was responsive with a significant change from study enrolment to ICU discharge (d = 0.8, P < 0.001), with IMS values increasing in 86% of survivors during ICU admission. No substantial floor (14% scored 0) or ceiling (4% scored 10) effects were present at ICU discharge. Conclusions: Our findings support the validity and responsiveness of the IMS as a measure of mobility in the ICU.